2009
DOI: 10.1016/j.diff.2008.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Lineage specification of Flk-1+ progenitors is associated with divergent Sox7 expression in cardiopoiesis

Abstract: SUMMARY Embryonic stem cell differentiation recapitulates the diverse phenotypes of a developing embryo, traceable according to markers of lineage specification. At gastrulation, the vascular endothelial growth factor (VEGF) receptor, Flk-1 (KDR), identifies a mesoderm-restricted potential of embryonic stem cells. The multi-lineage propensity of Flk-1+ progenitors mandates the mapping of fate-modifying co-factors in order to stratify differentiating cytotypes and predict lineage competency. Here, Flk-1 based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…A direct link between SOX7 expression and cardiogenesis has been previously examined (Nelson, Chiriac et al 2009). SOX family transcription factors have been implicated in the regulation of cardiac and/or vascular fate selection during early embryonic development (Naito, Shiojima et al 2006;Nelson, Chiriac et al 2009).…”
Section: The Mechanism Underlying the Effect Of Hpsc Aggregate Size Omentioning
confidence: 99%
See 2 more Smart Citations
“…A direct link between SOX7 expression and cardiogenesis has been previously examined (Nelson, Chiriac et al 2009). SOX family transcription factors have been implicated in the regulation of cardiac and/or vascular fate selection during early embryonic development (Naito, Shiojima et al 2006;Nelson, Chiriac et al 2009).…”
Section: The Mechanism Underlying the Effect Of Hpsc Aggregate Size Omentioning
confidence: 99%
“…SOX family transcription factors have been implicated in the regulation of cardiac and/or vascular fate selection during early embryonic development (Naito, Shiojima et al 2006;Nelson, Chiriac et al 2009). Bioinformatics analysis has revealed that the Wnt/β-catenin signaling pathway, which has been demonstrated to drive early progenitor cells into mature cardiomyocytes, is a target of SOX transcription factors (Faustino, Behfar et al 2008).…”
Section: The Mechanism Underlying the Effect Of Hpsc Aggregate Size Omentioning
confidence: 99%
See 1 more Smart Citation
“…SOX7 has been proposed as a potent activator in the endothelial differentiation of Flk-1 + cells (Yamauchi et al, 2007). Importantly, in the Flk1 + population, the vasculogenic Sox7 transcription factor is significantly up-regulated, overlapping with the emergence of the cardiac transcription factors Nkx2.5 and Gata4 (Nelson et al, 2009). Notably, sorting the parental Flk-1 + pool using the CXCR4/ Flk-1 biomarker pair, which is a predictor of the beginning of heart cell specification among pluripotent stem cells, reveals a divergent Sox7 expression, with significantly lower Sox7 expression in the cardiogenic subpopulation compared with the subpopulation enriched for endothelial and smooth muscle markers of vasculogenesis (Nelson et al, 2009).…”
Section: Sox7 In Vascular Development and Integration Of Vegf Signalimentioning
confidence: 99%
“…Notably, sorting the parental Flk-1 + pool using the CXCR4/ Flk-1 biomarker pair, which is a predictor of the beginning of heart cell specification among pluripotent stem cells, reveals a divergent Sox7 expression, with significantly lower Sox7 expression in the cardiogenic subpopulation compared with the subpopulation enriched for endothelial and smooth muscle markers of vasculogenesis (Nelson et al, 2009). Thus, differential Sox7 expression may be a potential regulatory switch in deciding between cardiac and vascular pathways in Flk1 + multi-lineage precursors (Nelson et al, 2009). Wnt/b-catenin appears to be a key signaling cascade that integrates the SoxF family, including Sox7, with the cardiovascular VEGF/Flk-1 and SDF1/CXCR4 pathways (Nelson et al, 2009).…”
Section: Sox7 In Vascular Development and Integration Of Vegf Signalimentioning
confidence: 99%